2005
DOI: 10.1063/1.1920419
|View full text |Cite
|
Sign up to set email alerts
|

Nanodot coupler with a surface plasmon polariton condenser for optical far/near-field conversion

Abstract: To transmit an optical signal to a nanophotonic device, a nanodot coupler was fabricated from a linear array of closely spaced metallic nanoparticles. To increase the optical far- to near-field conversion efficiency for transmission, a surface plasmon polariton (SPP) condenser was also fabricated from hemispherical metallic nanoparticles so that it worked as a “phased array”. The SPP was focused with a spot size as small as 400 nm at λ=785nm. When the focused SPP was incident into the nanodot coupler, its tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
108
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(110 citation statements)
references
References 12 publications
1
108
0
1
Order By: Relevance
“…A theoretical solution to this phenomenon was given by Gustav Mie in 1908 2,3 , who accurately solved for the scattering and absorption cross sections of spherical nanoparticles using equations from Maxwell's electromagnetic theory. Subsequently, monolayers of metal nanoparticles have been extensively used in surface plasmon resonance (SPR) sensors [4][5][6] , surface-enhanced Raman scattering (SERS) substrates 7,8 , and other plasmonic devices [9][10][11] . An interesting attribute of monolayers of metal nanoparticles (NP) synthesized on semiconductor substrates is the selective charging induced by Fermi level difference.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical solution to this phenomenon was given by Gustav Mie in 1908 2,3 , who accurately solved for the scattering and absorption cross sections of spherical nanoparticles using equations from Maxwell's electromagnetic theory. Subsequently, monolayers of metal nanoparticles have been extensively used in surface plasmon resonance (SPR) sensors [4][5][6] , surface-enhanced Raman scattering (SERS) substrates 7,8 , and other plasmonic devices [9][10][11] . An interesting attribute of monolayers of metal nanoparticles (NP) synthesized on semiconductor substrates is the selective charging induced by Fermi level difference.…”
Section: Introductionmentioning
confidence: 99%
“…Various plasmonic waveguide modes arise from the coupling of SPPs at the interfaces of metals and dielectrics. [1][2][3][4][5][6] Bozhevolnyi et al 7 reported a channel waveguide mode with a width of 1.1 m and a propagation length of 100 m. However, most of the experimentally realized plasmonic modes 1,7 have confinements in the micrometer range and do not reach deeply subwavelength dimensions. Thus they do not have obvious advantages compared to conventional dielectric waveguides.…”
mentioning
confidence: 99%
“…However, other excitation techniques need to be developed for launching SPPs in deeply subwavelength dimensions. For the excitation of lessconfined stripe wave guide modes, generators like arcshaped nanodots and slits were reported by Imre et al 3 and Nomura et al 4 Recently, two-dimensional, highly confined gap modes were experimentally realized by Chen et al 5 and Han et al 6 They showed the integration of slot waveguides with silicon dielectric waveguides via tapered couplers. However, the aforementioned excitation schemes often lack the compactness that is required for integration into subwavelength, plasmonic circuitry.…”
mentioning
confidence: 99%
“…2, we show two device designs: a coupler to convert an incident vortex beam of a given topological charge into a focused SPP wave and a conventional plasmonic lens for an incident Gaussian beam [18][19][20] . The performance of both structures is explored via finite-difference time-domain (FDTD) simulations using commercial software (Lumerical FDTD).…”
Section: Resultsmentioning
confidence: 99%